2011
DOI: 10.1002/dac.1315
|View full text |Cite
|
Sign up to set email alerts
|

Rain attenuation measurements over terrestrial microwave links operating at 15 GHz in Malaysia

Abstract: SUMMARY This paper presents the experimental results of rain rate and rain attenuation measurements on six terrestrial microwave links in tropical Malaysia. The rain attenuation data were collected from six DIGI MINI‐LINKs (DiGi Telecommunications Sdn. Bhd., Malaysia, Shah Alam, Selangor Darul Ehsan, Malaysia) operating at 15 GHz with 99.95 % availability. The experimental results were compared with the International Telecommunication Union Radiocommunication Sector (ITU‐R) method and other existing rain atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Substituting Equations (13) and (14) into Equation (12) yields the following R (mm/h) is the rain rate exceeded at 0.01 % of the time, r is the path reduction factor at the same time percentage, d (km) is the radio path length. Parameters k and  depend on frequency, rain temperature, and polarization, as earlier mentioned.…”
Section: Itu-r P 530-14 Modelmentioning
confidence: 99%
“…Substituting Equations (13) and (14) into Equation (12) yields the following R (mm/h) is the rain rate exceeded at 0.01 % of the time, r is the path reduction factor at the same time percentage, d (km) is the radio path length. Parameters k and  depend on frequency, rain temperature, and polarization, as earlier mentioned.…”
Section: Itu-r P 530-14 Modelmentioning
confidence: 99%
“…Rainfall is a significant impediment that obstructs the propagation of mm‐wave signals from transmitter to receiver. Millimeter‐wave signals can be absorbed, scattered, depolarized, and diffracted by rain . This can restrict the propagation of mm‐wave signals, causing high signal attenuation loss through the effective propagation path length (km) measured in dB/km.…”
Section: Introductionmentioning
confidence: 99%
“…Rain attenuation harshly increases when the frequency, rain density, or effective length are increased. This attenuation reduces the reliability, availability, and degraded the overall performance of the communications link . As a result, rain attenuation is a real and concerning issue facing the implementation of mm‐waves, especially in tropical regions with consistent heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainfall attenuation measurement via terrestrial communication link at the frequency of 15 GHz in Malaysia was presented in [3]. Four prediction methods were compared, and it was concluded that ITU-R P.530-13 model underestimated the measured rain attenuation values, while revised Moupfouma's model and Lin model overestimated the measured rain attenuation values.…”
Section: Introductionmentioning
confidence: 99%